Effects of a season of intercollegiate basketball on various fitness measures of women players - Hilgenberg, Heidi (My University, 1988)
This study examined the effects of a season of intercollegiate basketball on various fitness measures of women players. Weight, body composition, aerobic fitness, peak anaerobic power, and vertical jump height were analyzed through the use of five separate tests. These five tests were administered before and after the playing season to 11 members of the University of Wisconsin - La Crosse Women's Basketball Team. The preseason tests were conducted before regular team practice began, while the postseason tests were completed two weeks following the last competitive game. A dependent t - test revealed only one significant difference, (p<.05), in this study. The significant difference was a reduction in body fat percentage.
Keywords: Basketball for women -- Physiological aspects